Sosialisasi Head Up 30 Derajat Pada Keluarga Pasien Dengan Stroke Hemoragic Di Rumah Sakit Dr R Soeharsono Banjarmasin - ., Ernawati; Sri Purwanti Ariani; Nor Aina (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
Stroke is the loss of brain function caused by the interruption or reduction of blood supply to the brain, resulting in sudden, progressive, and rapid onset of local or global nerve dysfunction. Impaired blood flow in stroke patients can lead to hemodynamic disturbances, including oxygen saturation. One self-care nursing intervention to improve oxygen saturation is providing a 30-degree head-up position.